The Perceptions of Principals on The Phasing Out of Accounting in Secondary Schools in Limpopo Province South Africa - Ndou, Muhali (Indonesian Accounting Research Journal, 2023)
Accounting is facing extinction in some schools in Limpopo Province South Africa because of poor performance by learners. This phasing out of accounting developed curiosity in researchers to start with this investigation. The principals’ reflections and experiences were examined in the study on the phasing-out of accounting as in Limpopo Province schools. The empirical and conceptual nature of the study employed the qualitative approach. The study used interview and observations techniques to collect data from ten secondary schools’ principals in Limpopo province coming from different districts that once had accounting. The findings revealed that teachers’ poor performance and learners’ high failure rate in accounting that caused fewer learners in taking it, resulted in the subject being phased out in some schools. The non-accounting teachers teaching EMS in grade 8 and 9 coupled with inadequate pedagogical content knowledge were found to be amongst the primary contributors in the phasing out of accounting. The hostile working environment due to overloading coupled with lack of strategic school resources and infrastructure contributed to the phasing out of accounting. This study recommends that adequately qualified educators should teach accounting from Senior to Further Education and Training Phases. Lastly, teaching and learning resources and provisioning of subject advisors’ and motivation by professionals in the accounting field need to be addressed.